Risk factors in the oil industry: un upstream and downstream analysis - Ramos, S.; Veiga, H.; Wang, C.W. (The Interrelationship Between Financial and Energy Markets, 2014)
In this paper we examine the drivers of stock market value in the upstream (producers) and downstream segments (petroleum refiners) of the oil industry. Using a sample of U.S. firms we find that stock returns of upstream and downstream firms follow stock market and oil price returns. Moreover, the upstream firm stock returns are sensitive to changes in the Canadian dollar, an important oil trade partner of the U.S., to natural gas returns and its volatility, but not to oil return volatility. Both the upstream and downstream segments present asymmetric changes regarding oil return changes. Stock returns of the oil industry respond asymmetrically to oil returns, i.e., positive oil returns had a greater impact than oil price drops in the period 1998–2004. Before 1997 we do not find any asymmetric effects, and after 2004, they are only statistically significant in the upstream segment. Overall, the evidence for asymmetric effects is more consistent across measures and time in the upstream than in the downstream segment.